Polyaniline (PAni) optical sensor in chloroform detection - Mohamad Ahad, Irma Zulayka; Harun, Sulaiman Wadi; Gan, Seng Neon; Phang, Sook Wai (Elsevier, 2018)
A novel Fiber Bragg grating (FBG) coated with PAni film was used as a sensitive optical sensor for chloroform detection. In this study, the effect of synthesis parameters such as different dopant ratios (Ani: AOT = 5: 3, 5: 5 and 5: 7) and different polymerization temperatures (–5 °C, 0 °C and 25 °C) toward the efficiency of sensors were being investigated. Among the PAnis, PAni 5: 5 (0 °C) possessed the highest conductivity (1.627 × 10−2 S/cm) and the best efficiency (sensitivity = 0.0015) with response time of 7 s. The mechanism during chloroform detection was studied through Fourier Transform Infrared (FTIR) and Ultraviolet-visible (UV–vis) analysis, and the results showed clearly the physical interaction of the partial negative charge (Clδ−) of chloroform with the partial positive charge (NHδ+) on PAni chain. Besides, the sensor performance such as recyclability, selectivity, limit of detection (LOD), limit of quantitation (LOQ) and real sample analysis was studied in details in this study.